ANALISIS HUKUM ISLAM TERHADAP FENOMENA PERNIKAHAN DINI DI PESANTREN DARUL ISTIQAMAH LAPPA’E KABUPATEN SINJAI - Syahida Asia; Hasan, Hamzah; Mustafa, Zulhas’ari; Zulfahmi; Idrus, Achmad Musyahid (MADDIKA : Journal of Islamic Family Law, 2024)
This study aims to find out the practice of early marriage, express the community’s views on early marriage and make an analysis based on Islamic law about the practice of early marriage in the Darul Istiqamah Lappa'e Islamic Boarding School, Sinjai. This research is a field study using a descriptive qualitative approach. The results of the study show that early marriage at the Darul Istiqamah Lappa’e Islamic Boarding School is based on parental approval and encouragement. In addition, the community views early marriage in Islamic boarding schools as a positive thing because it aims to foster young people to achieve piety and avoid promiscuity that is contrary to Islamic teachings. According to Islamic law, early marriage at the Darul Istiqamah Islamic Boarding School does not violate religious law because it is considered a solution to prevent greater dangers, such as adultery or pregnancy out of wedlock, by referring to the rules of Dar’u al-Mafasid. In addition, early marriage is carried out with the consent of the students themselves without coercion, with various considerations of benefits, namely efforts to achieve greater goodness and benefits.